A violência contra a mulher negra no âmbito familiar: um diálogo necessário em torno da região Amazônica oriental do Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2024)
This research work is a bibliographic survey whose main goal is to research about domestic violence committed against Black women in the Amazon Region. A fundamental concept for the analysis proposed by this research is the Intersecionality, which means to add race, social class and geolocalization to better understand the reality of Women of Color, overall, those that live in the Brazilian Amazon, who represent the main subject of this body of work. Considering the growth of national and regional statistics for women violence in the Amazon, this research aims to seek for the main contributions found in the Brazilian Laws for the Protection of Women, to those who are victims of Domestic and Familial Violence. Based on the data showed in the article, it’s clear that the growth seen in the statistics for Women Violence are caused and catalysed by the hyper social vulnerability, which means the combination of poverty, unemployment, social exclusion and isolation that target those women who live in the Amazon, making their quality of life considerably worse than in the rest of Brazil and also making them potentially more vulnerable to domestic violence.
Keywords: Violência contra a mulher - Direitos das mulheres; Violência doméstica - Proteção legal; Direitos da Mulher - Legislação brasileira; CNPQ::CIENCIAS SOCIAIS APLICADAS.; ODS 10 – Redução das desigualdades; ODS 16 – Paz, justiça e instituições eficazes; ODS 5 – Igualdade de gênero